Survey Pembinaan olahraga dayung di jawa tengah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2012)
Olahraga dayung merupakan cabang olahraga air yang menggunakan peralatan berupa dayung dan perahu. Untuk menjadi pendayung yang baik dan berprestasi diperlukan latihan pembinaan secara teratur dan terus menerus. Olahraga dayung          di Indonesia belum bisa dibanggakan, sehingga perlu dicarikan jalan pemecahannya. Dengan adanya PODSI sebagai induk organisasi dayung di Indonesia, diharapkan dapat meningkatkan pembinaan olahraga dayung di Indonesia, sehingga prestasi olahraga dayung dapat dibanggakan. Untuk mengetahui pembinaan olahraga dayung di Jawa Tengah, maka permasalahan dalam penelitian ini adalah bagaimana program latihan yang dilaksanakan pada kegiatan olahraga dayung di Jawa Tengah, bagaimana sarana dan prasarana olahraga dayung di Jawa Tengah, bagaimana organisasi olahraga dayung di Jawa Tengah, bagaimana prestasi yang dicapai olahraga dayung di Jawa Tengah tahun 2011/2012. AbstractRowing is a water sport that uses equipment such as paddles and boats. To be       a good rower and perform necessary coaching exercises regularly and continuously. Rowing in Indonesia can not be proud of that necessary to find the solution. With the paddle PODSI as the parent organization in Indonesia, is expected to increase coaching rowing in Indonesia, so that achievement can be proud of rowing. To learn coaching rowing in Central Java, the problem of this research is how the training program was held on rowing activities in Central Java, how to paddle sports facilities and infrastructure in Central Java, how the organization rowing in Central Java, how achievement rowing in Central Java in 2011/2012.This study used a qualitative descriptive method. Which is the object of this research is rowing in Central Java, while the subjects in this study is the coach rowing and canoeing, as well as the athlete’s general chairman. Methods of data collection in this study used interviews, observation and documentation. Data analysis techniques in this study using three interrelated components, namely data reduction, data presentation, and drawing conclusions tri anggulasi and verification.